Source-separating wastewater systems as an alternative to replacing the existing sewer network: a proposed conceptual framework - Letty Mora Chirito; Inga Herrmann; Elisabeth Kvarnström; Annelie Hedström (Journal of Environmental Management, 2026)

Nutrient concentration of blackwater digestate with a pilot-scale low-temperature evaporator - Stephanie Rusch Fehrmann; Hamse Kjerstadius; Inga Herrmann; Annelie Hedström; Andreas Johansson; Elisabeth Kvarnström (Journal of Water Process Engineering, 2026)

Performance of a green wall in treating organics, nutrients and pathogens in greywater in a cool climate - Mashreki Sami; Annelie Hedström; Elisabeth Kvarnström; David T. McCarthy; Heinz Gattringer; Marco Hartl; Inga Herrmann (Journal of Water Process Engineering, 2026)

Phthalates and pharmaceuticals in soil, groundwater, and surface water downgradient of a wastewater soil infiltration system - Rasmus Klapp; Inga Herrmann; Annelie Hedström; Noora Perkola; Marja Hagström; Hanna Niemikoski; Juho Kinnunen; Pekka Rossi; Elisangela Heiderscheidt (Journal of Hazardous Materials, 2026)

Nutrient concentration of blackwater digestate using an air gap membrane distillation process - Stephanie Rusch Fehrmann; Annelie Hedström; Elisabeth Kvarnström; Juan Antelo; Iemke Bisschops; Inga Herrmann (Journal of Water Process Engineering, 2024)

Treatment of greywater and presence of microplastics in on-site systems - Mashreki Sami; Annelie Hedström; Elisabeth Kvarnström; Heléne Österlund; Kerstin Nordqvist; Inga Herrmann (Journal of Environmental Management, 2024)

Real-world characteristics and use patterns of patients treated with vericiguat: A nationwide longitudinal cohort study in Germany - Fabian Kerwagen; Christoph Ohlmeier; Thomas Evers; Stefan Herrmann; Inga Bayh; Alexander Michel; Silvia Kruppert; Joanna Wilfer; Rolf Wachter; Michael Böhm; Stefan Störk (European Journal of Clinical Pharmacology, 2024)
Purpose Vericiguat reduced clinical endpoints in patients experiencing worsening heart failure in clinical trials, but its implementation outside trials is unclear. Methods This retrospective analysis of longitudinally collected data was based on the IQVIA™ LRx database, which includes ~ 80% of the prescriptions of the 73 million people covered by the German statutory health insurance. Results Between September 2021 and December 2022, vericiguat was initiated in 2916 adult patients. Their mean age was 73 ± 13 years and 28% were women. While approximately 70% were uptitrated beyond 2.5 mg, only 36% reached 10 mg. Median time to up-titration from 2.5 mg to 5 mg was 17 (quartiles: 11–33) days, and from 2.5 to 10 mg 37 (25–64) days, respectively. In 87% of the patients, adherence to vericiguat was high as indicated by a medication possession ratio of ≥ 80%, and 67% of the patients persistently used vericiguat during the first year. Women and older patients reached the maximal dose of 10 mg vericiguat less often and received other substance classes of guideline-recommended therapy (GDMT) less frequently. The proportion of patients receiving four pillars of GDMT increased from 29% before vericiguat initiation to 44% afterwards. Conclusion In a real-world setting, despite higher age than in clinical trials, adherence and persistence of vericiguat appeared satisfactory across age categories. Initiation of vericiguat was associated with intensification of concomitant GDMT. Nevertheless, barriers to vericiguat up-titration and implementation of other GDMT, applying in particular to women and elderly patients, need to be investigated further.

From Diverse Perspectives to Unified Strategies: European University Alliances and the Development of Adaptable Science Communication Concepts - Vanessa J. Herrmann; Annabell Heimer; Inga-Maria Eichentopf; Gunter Süß (BHM Berg- und Hüttenmännische Monatshefte, 2024)
Communicating scientific subjects to non-academic, non-specialist, or very young audiences using various event formats (lecture series, panel discussions, science slams, Children’s Universities, Citizen Universities, etc.) is a key aspect of science communication. In the EURECA-PRO University Alliance, the implementation of these kinds of formats will be given greater focus at all institutions to make significant topics accessible in ways that go beyond the institutional walls of the universities. To this end, approaches are being developed and tested to identify and reduce existing hurdles for the public. At the same time, in an international structure such as EURECA-PRO, it is essential to know individual frameworks to ensure that measures promoting a uniform strategy can be implemented by everyone. In order to develop adaptable strategies for universities with different thematic focuses and locations in Europe, certain conditions for success must be identified and considered. In addition to the needs and resources of target groups, the requirements, and opportunities of the universities—as dictated by their respective circumstances—must also be considered. Using the examples of the EURECA-PRO partners Technical University of Crete in Chania (TUC), Silesian University of Technology in Gliwice (SUT), and Montanuniversität Leoben (MUL), challenges and results will be discussed.

Treatment efficiency of package plants for on-site wastewater treatment in cold climates - Brenda Vidal; Juho Kinnunen; Annelie Hedström; Elisangela Heiderscheidt; Pekka Rossi; Inga Herrmann (Journal of Environmental Management, 2023)

Factors affecting effluent quality in on-site wastewater treatment systems in the cold climates of Finland and Sweden - Juho Kinnunen; Pekka M. Rossi; Inga Herrmann; Anna-Kaisa Ronkanen; Elisangela Heiderscheidt (Journal of Cleaner Production, 2023)

Polymer-assisted hydraulic dredging for quality control of stormwater pond sediment and reject water – Influence of polymer choice and its preparation - Fredrik Nyström; Inga Herrmann; Annelie Hedström; Maria Viklander (Journal of Water Process Engineering, 2023)

Enhancing the Reliability of Laboratory Phosphorus Filter Tests: Effect of Influent Properties and Interpretation of Effluent Parameters - Inga Herrmann; Amir Jourak; Annelie Hedström; Staffan Lundström; Maria Viklander (Water, Air, & Soil Pollution, 2014)

Longitudinal Dispersion Coefficient: Effects of Particle-Size Distribution - Amir Jourak; Vilnis Frishfelds; J. Gunnar I. Hellström; T. Staffan Lundström; Inga Herrmann; Annelie Hedström (Transport in Porous Media, 2013)